2004
DOI: 10.2134/jeq2004.6450
|View full text |Cite
|
Sign up to set email alerts
|

Fertilizer Source Effect on Ground and Surface Water Quality in Drainage from Turfgrass

Abstract: Nutrients in surface and ground water can affect human and aquatic organisms that rely on water for consumption and habitat. A mass-balance field study was conducted over two years (July 2000-May 2001) to determine the effect of nutrient source on turfgrass runoff and leachate. Treatments were arranged in an incomplete randomized block design on a slope of 7 to 9% of Arkport sandy loam (coarseloamy, mixed, active, mesic Lamellic Hapludalf) and seeded with Kentucky bluegrass (Poa pratensis L.) and perennial rye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
135
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(154 citation statements)
references
References 48 publications
12
135
2
Order By: Relevance
“…In general, few studies have addressed the effects of adding slow-and controlled-release fertilizers on runoff in agronomic crops. Research on turfgrass indicates that slow-and controlled-release fertilizers may be effective in reducing N in runoff during the first year of turfgrass establishment, but not in subsequent years (10). Nitrogen concentrations in floodwater used in rice production were lower when sulfur-coated urea was applied compared to urea and ammonium sulfate fertilizer applications (7).…”
Section: Slow-and Controlled-release Fertilizersmentioning
confidence: 99%
“…In general, few studies have addressed the effects of adding slow-and controlled-release fertilizers on runoff in agronomic crops. Research on turfgrass indicates that slow-and controlled-release fertilizers may be effective in reducing N in runoff during the first year of turfgrass establishment, but not in subsequent years (10). Nitrogen concentrations in floodwater used in rice production were lower when sulfur-coated urea was applied compared to urea and ammonium sulfate fertilizer applications (7).…”
Section: Slow-and Controlled-release Fertilizersmentioning
confidence: 99%
“…In contrast, the geochemical signature of groundwater beneath turfgrass in residential lawns has not been determined in this region. Furthermore, studies of nitrate loss from turfgrass management often involve controlled field experiments with vadose-zone monitoring (e.g., Easton and Petrovic, 2004;Frank et al, 2006;Frank, 2008;Geron et al, 1993;Guertal and Howe, 2012;Guillard and Kopp, 2004;Mangiafico and Guillard, 2006;Morton et al, 1988). Survey data, however, suggest that actual suburban fertilizer usage may not be well represented by controlled studies and can be highly variable (Law et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…research to evaluate residential landscape models for their potential to reduce N leaching. As a result, recent studies have demonstrated the potential for residential landscape models (i.e., vegetation type and associated maintenance regimes) to infl uence N leaching (Hipp et al, 1993;Broschat, 1995;Erickson et al, 2001;Bowman et al, 2002;Easton and Petrovic, 2004;Frank et al, 2005;Amador et al, 2007). Currently, the predominant residential landscape model in Florida consists of a monoculture of St. Augustinegrass [SA; Stenotaphrum secundatum (Walt.)…”
mentioning
confidence: 99%